2001
DOI: 10.1021/ac015558j
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Decarboxylation of Tyrosine and Phenylalanine To Enhance Volatility for High-Precision Isotopic Analysis

Abstract: We present a rapid and selective method to increase the volatility of tyrosine and phenylalanine without adding derivative C for high-precision gas chromatography-continuous-flow isotope ratio mass spectrometry (GCC-IRMS) based on enzymatic decarboxylation to yield alkylamines and evaluated for 15N isotopic integrity. Purified tyrosine and phenylalanine were converted to tyramine and phenethylamine by tyrosine and phenylalanine decarboxylases, respectively. GC separation was achieved using a thick stationary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…modifications are decarboxylation [108,109], reduction of fatty acid esters to alcohols [110], reduction of organometal (loid) oxides to the corresponding hydrides [111], intramolecular esterification [112], or selective fragmentation [89]. Besides enabling carbon-isotope analysis, the latter approach has been shown to facilitate isotope analysis of nitrogen and hydrogen also [65,89].…”
Section: Chemical Modification Without Addition Of Protecting Groupsmentioning
confidence: 99%
“…modifications are decarboxylation [108,109], reduction of fatty acid esters to alcohols [110], reduction of organometal (loid) oxides to the corresponding hydrides [111], intramolecular esterification [112], or selective fragmentation [89]. Besides enabling carbon-isotope analysis, the latter approach has been shown to facilitate isotope analysis of nitrogen and hydrogen also [65,89].…”
Section: Chemical Modification Without Addition Of Protecting Groupsmentioning
confidence: 99%
“…The turnover rate of the catalyzed reaction (TDC = tyrosine decarboxylase) normalHO normalC 6 normalH 4 normalCH 2 normalCH false( normalNH 2 false) normalCOOH + normalH 2 normalO TDC HO normalC 6 normalH 4 CH 2 CH 2 NH 2 + CO 2 can, at the incubation pH of 5.5, easily be controlled by measuring the volume of the produced CO 2 . Ziadeh et al used enzymes from S. faecalis for the selective conversion of l -phenylalanine and l -tyrosine into the corresponding amines for a selective δ 15 N value determination. Although the authors found no difference between the δ 15 N values of the amino acids and the extracted amines, we do not believe that the applied ethanol extraction of tyramine at pH 5.5 is quantitative, because the compound is amphoteric.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymatic decarboxylation of phenylalanine and tyrosine increased their volatility for determination of d 15 N by CF-SIRMS without introducing extraneous C or significant fractionation. 315 Increased CO 2 : N 2 ratios would have prevented the use of cryotraps and degraded the chromatographic performance. The reproducibility (1s) of d 15 N was ¡0.33% and there was no significant difference between values measured on decarboxylated amino acids and those determined on intact amino acids by EA-SIRMS.…”
Section: Sample Preparationmentioning
confidence: 99%